Analysis of the Application of Financial Accounting Standards of Small and Medium Entities (SAK EMKM) and Cooperatives in the Preparation of Financial Statements at Cooperative Saves and Loans in Bengkulu City - Lesi Dwiantini; Neri Susanti; Nenden Restu Hidayah (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the application of financial accounting standards for micro, small and medium entities (SAK EMKM) and cooperatives in preparing financial statements at the Bengkulu City Joint Business Savings and Loan Cooperative. Data collection tools are carried out by means of documentation and unstructured interviews. The analytical method used is a comparative analysis comparing SAK EMKM and cooperatives will be compared with the application of accounting at the Joint Venture KSP Bengkulu City. Based on the results of research regarding the Analysis of the Application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) and Cooperatives in the Preparation of Financial Statements at the Bengkulu City Joint Business Savings and Loans Cooperative, it can be concluded that the implementation of SAK EMKM in the Joint Venture KSP has been going well because partly large in accordance with SAK EMKM. Meanwhile, there are two items that do not meet SAK EMKM, namely the notes on the financial statements because the Joint Venture KSP has not made notes on the financial statements and the income statement which does not include a tax expense account.